PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR SISWA - Enni Mepra; Eni Sumanti Nasution; Kasmawati Kasmawati (Gravity Journal, 2023)
This study aims to determine the Improvement of Class VIII Student Learning Outcomes at SMP Negeri 4 Sinunukan by using the Team Assisted Individualization (TAI) Learning Model. The research was conducted in a quasi-experimental manner. The population of this study was students of class VIII at SMP Negeri 4 Sinunukan. This type of research is class action research (CAR) or called Classroom Action Research which is reflective, participatory, and collaborative with the cycle method. Action research includes qualitative research, researchers will use instruments for data collection. Data analysis techniques use quantitative data using gain values. While the instruments used through tests for learning outcomes, observation through questionnaires and interviews. The conclusion in this learning research is that student learning outcomes increase from Pre-Cycle, Cycle I and Cycle II, that is, seen from the pre-cycle average score (47.78) increasing in cycle I (67.41) and continuing to increase in cycle II (84.44) and completeness learning outcomes Pre-cycle is 4 people, Cycle I is 16 people and cycle II is 24 people